STRATEGI PENGOLAHAN MULTIKULTURALISME DI PESANTREN DALWA DAN SIDOGIRI PASURUAN - Dewi Masita; Unun Zumairoh ASR Himsyah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This study aims to know and analyze in depth how the Management Strategy of multiculturalism of Dalwa and Sidogiri pesantren in Pasuruan? This research methodology uses a Sociology approach. The process of data collection through interviews, observation, and documentation. Technical data analysis through the stages of Horizontalizatio, Deveping clusters of meaning, Textural description, Structural decription, and Essentialization The theory used as an analytical tool is the theory of multiculturalism. The results showed that in the two pesantren first, apply multicultural as understanding, appreciation, and assessment of one's culture as well as respect and curiosity about the culture of students from several regions in Indonesia and abroad. Second, its multicultural application that is able to make students think dialectically, make students understand each other, and dialogue and interact with fellow students from different regions of origin and outside communities and make students able to think globally and locally. Third, in applying multicultural to each pesantren, Pesantren Dalwa and Pesantren Sidogiri have a distinctive rationale for multicultural application, namely pesantren Dalwa with Ahlus Sunnah Wal Jamaah Alawiyin, and pesantren Sidogiri Ahlus Sunnah Wal Jamaah Nahdliyah.